ANALISIS VIDEO PENGAJARAN MIKRO MAHASISWA PRODI BAHASA MANDARIN FKIP UNIVERSITAS TANJUNGPURA ANGKATAN 2019 - Edwin, Steven; Ina, Ina; Suhardi, Suhardi (Universitas Tanjungpura, 2023)
Teaching methods and teaching steps are the second element to achieve the teaching goals in classroom teaching. If the teaching methods and steps are unsuitable, the student's learning and thinking methods will be affected. Chinese Language Education Study Program, Language and Art Education Department, Teacher Training and Education Faculty, Tanjungpura University provides a platform for fifth-semester students to practice their teaching abilities and skills through micro-teaching classes. In order to be a successful teacher, a prospective teacher must be able to master both aspects. The research object of this paper is the micro-teaching video of the 2019 students majoring in the Chinese Language Education Study Program, Language and Art Education Department, Teacher Training and Education Faculty, Tanjungpura University. The research in this paper is quantitative. The author conducts the observation method to observe and analyze the micro-teaching videos of the 2019 students majoring in the Chinese Language Education Study Program, Language and Art Education Department, Teacher Training and Education Faculty, Tanjungpura University. Through analysis, the author found that prospective teachers' teaching methods and teaching steps could be more varied in design, which is related to the lack of knowledge and understanding of prospective teachers on teaching methods and teaching steps.